Assessment of Day Care Centers under Public Mental Health Program in a District of Kerala: An Observational Study - Ramkumar G. Sathiaseelan; R Prasad Kumar (Indian Journal of Social Psychiatry)
Introduction: Day care is a component of service provisioning for persons with severe mental illness living in the community. This study assesses day care centers under a public mental health program in a district of Kerala. Methods: We did a documentary review of program documents to describe how the day care program had envisaged its structure, function, and expected outcome. Field visits were made to assess the centers on the same attributes. The lead staff members and all program attendees were interviewed. The sociodemographic and clinical profile was assessed while disability was measured using the WHODAS 2.0 12-item Scale. Results: The two centers were assessed 8 years after their inception. The centers functioned as drop-in-type social care facilities located on local government premises, and each center was serviced by a nursing personnel, a nursing attendant, and a social work personnel who worked as an occupational therapist and program coordinator for both centers. The estimated cost of running each center was 20 lakhs/year. Occupational therapy activities were geared toward day engagement and did not aspire to impart vocational skills or employment opportunities onsite or outside and almost all work-based occupational therapy activities fizzled out after a limited trial. Centers catered to both persons with mental illness and intellectual developmental disorders. There was no formal exit plan for the attendees, the mean duration of attendance was 4.4 ± 2.63 years, the total attendees since inception were 75, and the currently active number was 28. Nonspecific reasons and family inconvenience were noted as reasons for disengagement. Disability assessment revealed a mean score of 8.45 ± 6.8 (median 6.5, range 0–27), indicating low levels of disability, although 60% were formally certified with median disability of 60%. Overall, staff opined, based on their interactions with the attendees’ families, that day care attendance offered benefits over routine outpatient care in terms of providing a meeting place outside the home for recreation and socialization. Discussion: Our assessment concludes that the modest benefits that attendees get from the centers are derived largely from the socializing and companionship that the meeting place provides. We suggest that more such drop-in centers can be started with a lesser cost outlay while at the same time upgrading the existing ones with more resources to derive greater benefits than from the current meeting place orientation.